Pengaruh Implementasi Inovasi Digital Dan Lingkungan Kerja Terhadap Efektivitas Kerja Karyawan Studi: Karyawan PT. Tiki Jne Exspress Cabang Utama Kota Sukabumi - Siti Resna Wulandari S; Erry Sunarya; Faizal Mulia Z (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Effevtiveness within the scope of the organization or company is generally associated with the implantation of activities aimed at promoting and developing the organization or campany. This study aims to determine the effect of digital innovation implementation and the work environment having an influence that can increase the work effectiveness of employee at PT. TIKI JNE. The research method used is quantitative research method and the sample technique used is saturated sample technique. Data were obtained through questionnaires which were distributed to 58 respondents who were employees of PT. TIKI JNE with Likert scale measurements. The results of the hypothesis test stated that the influence of digital innovation implementation had a positive and significant effect on employee work effectiveness. The results of hypothesis testing stated that work environment has a positive and significant effect on employee work effectiveness. Implementation of the application used is also very helpful for employees in managing work, especially regarding personnel administraton and the work environment that exist around employees greatly influence the work carried out on the effectiveness of employee work. Keyword: Digital Innovation Implementation, Work Environment, Employee Effectiviness